Implementation of measures to counteract cyber threats and abuse in information security based on blockchain technologies - Brynza, N.; Borodavka, V.; Teslenko, О. (ХНУРЕ, 2025)
The selection of security methods for the ISMS of blockchain systems has been researched and justified, considering their specifics and the nature of threats. The key selection factors include ensuring reliability, decentralization, confidentiality, and cyberattack resilience. Various approaches were examined, including consensus algorithms, cryptographic methods, smart contract security, and network protocols. Based on the analysis, the implementation of a monitoring and response method was deemed appropriate, specifically utilizing tools such as iptables, ipset, fail2ban, and dynamic blacklists of IP addresses. This mechanism effectively combines various tools for automation and dynamic updating of security levels. By employing iptables and ipset, the system efficiently filters network traffic, while fail2ban monitors suspicious patterns and blocks malicious IP addresses based on configurable rules. The inclusion of dynamic blacklists adds an extra layer of protection by continuously updating the database of known malicious IP addresses, allowing real-time security adjustments. Monitoring results demonstrate that the system's effectiveness can vary significantly depending on the number of blocked attacks, the cyberattacks that bypassed the system, and the false positive rate. У роботі здійснено аналіз і аргументовано обрано методи захисту, що враховують особливості блокчейн-систем та специфіку потенційних кіберзагроз. Вибір підходів ґрунтувався на потребі забезпечення високої надійності, децентралізованого управління, конфіденційності даних і стійкості до атак. Розглядалися різноманітні захисні стратегії, включаючи консенсусні алгоритми, криптографічні засоби, захист смарт-контрактів і особливості мережевої взаємодії. За результатами порівняльного аналізу доцільним виявилось застосування моніторингово-реагувальної моделі із використанням таких інструментів, як iptables, ipset, fail2ban і механізми динамічного формування чорних списків IP-адрес. Запропоноване рішення дозволяє поєднати ці засоби в єдину систему автоматизованого управління рівнями безпеки. Зокрема, iptables та ipset відповідають за ефективне фільтрування трафіку, fail2ban виявляє та блокує підозрілу активність, а динамічні чорні списки забезпечують оперативне оновлення бази загроз і адаптацію системи до нових викликів у реальному часі. Проведене тестування свідчить, що ефективність системи значною мірою залежить від кількості заблокованих атак, рівня проникнення загроз і частоти хибних спрацювань.
Keywords: web service; blockchain; cybersecurity; cyberattack; information security management system; security mechanism; блокчейн; кіберзахист; система управління інформаційною безпекою; механізм захисту; механізм захисту; механізм захисту